Spiralin-like protein SLP31 from Spiroplasma eriocheiris as a potential antigen for immunodiagnostics of tremor disease in Chinese mitten crab Eriocheir sinensis - Meng, Q; Gu, W; Bi, K; Ji, H; Wang, W (Folia microbiologica, 2010)
Spiroplasma eriocheiris caused massive mortality of Chinese mitten crab Eriocheir sinensis but little is known about the molecular characteristics of this microorganism. We described here the identification of a spiralin-like protein (SLP31) from S. eriocheiris and expression in Escherichia coli. Analysis of the nucleotide sequence revealed that the clone has an open reading frame of 837 bp encoding a protein of 279 amino acids. Theoretical isoelectric point and molar mass for SLP31 are 7.72 and 31 kDa, respectively. The similarity of SLP31 deduced amino acid sequence shared with the spiralin from other species indicated that the gene may be a member of spiralin family. The TGA codon in Spiroplasma serves not as a stop signal but as a code for the amino acid tryptophan. After cloning the SLP31, the gene was site-mutated from TGA to TGG and transcribed in E. coli to full expression of SLP31. The purified recombinant protein was used to determine the immune reactivity by Western blotting which suggests that SLP31 could be a good antigen for immunodiagnostic of tremor disease in E. sinensis.
Keywords: financování organizované; Animals; Immunoassay; otevřené čtecí rámce; Base Sequence; Spiroplasma; antigeny bakteriální; sekvenční homologie; proteiny vnější bakteriální membrány; Escherichia coli; Blotting, Western; China; DNA bakterií; sekvence aminokyselin; bakteriologické techniky; Bacteriological Techniques; Bacterial Outer Membrane Proteins; DNA, Bacterial; shluková analýza; Molecular Sequence Data; Amino Acid Sequence; Isoelectric Point; Brachyura; Sequence Homology; Financing, Organized; Phylogeny; western blotting; krabi; molekulární sekvence - údaje; molekulová hmotnost; Cloning, Molecular; imunoanalýza; izoelektrický bod; sekvence nukleotidů; Čína; Antigens, Bacterial; Sequence Analysis, DNA; klonování DNA; Open Reading Frames; zvířata; sekvenční analýza DNA; Molecular Weight; Cluster Analysis; fylogeneze